2013
DOI: 10.1227/neu.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of 127 Anterior Choroidal Artery Aneurysms A Cohort Study of Resultant Ischemic Complications

Abstract: The ischemic complication rate from surgical treatment of AChA aneurysms is most closely associated with higher frequency of temporary clip applications for proximal control and may be lower than previously reported. Supplementary intraoperative tools and limitation of vessel manipulation should be used to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Causes of the AChA syndrome after surgery mainly include excessive turbulence of blood vessels during surgery, thromboembolism of the AChA and its branches, edema, clip displacement, vasospasm, and reduction of the collateral blood supply. 12,[15][16][17][18] In recent years, many authors have used a variety of methods for detection of accidental AChA obliteration by the clip: intraoperative angiography, muscle motor evoked potentials monitoring 19 ; and intraoperative micro Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of the AChA syndrome after surgery mainly include excessive turbulence of blood vessels during surgery, thromboembolism of the AChA and its branches, edema, clip displacement, vasospasm, and reduction of the collateral blood supply. 12,[15][16][17][18] In recent years, many authors have used a variety of methods for detection of accidental AChA obliteration by the clip: intraoperative angiography, muscle motor evoked potentials monitoring 19 ; and intraoperative micro Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…reported that ischemic complications stemming from surgical treatment of AChA aneurysms are most closely associated with a higher frequency of temporary clip applications for proximal control. [ 4 ] To preserve the AChA and avoid severe hemiparesis, monitoring with ICG-VAG and MEP is very useful. ICG-VAG is a safe and effective method that provides necessary information for modifying clip placement immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with clipping, coiling AChA aneurysms had a significantly lower incidence of AChA infarction 27 . For instance, in a study performed by Bohnstedt et al in 2013, the ischemic complication rate following surgical treatment of AChA aneurysms was 12%, whereas coiling AChA aneurysms as an alternative to clipping was associated with a 5.5% risk of ischemia 28 .…”
Section: Aneurysmmentioning
confidence: 99%